Existential crisis and the power of love in a family affected by dementia: – a sister's experiences - Damsgaard, Janne Brammer; Kvande, Monica Evelyn; Delmar, Charlotte; Lauritzen, Jette (Nordisk Tidsskrift for Helseforskning, 2025)
The essay sheds light on existential crisis and love within a family affected by dementia, viewed from a sister's perspective. Through examples, it highlights family dynamics such as powerlessness, disappointment, and grief. These relational and psychological dynamics occur «beside» the person with dementia and are identity-altering, potentially influencing roles and values within the family. The essay incorporates reflections on love and vulnerability from theologian and philosopher Knud Ejler Løgstrup and nurse and philosopher Kari Martinsen. It points out how these phenomena are fundamental prerequisites for people to relate to one another. Such insights can serve as a driving force for existential serenity in a world filled with uncertainty and chaos for those close to people with dementia. By balancing perception and understanding and focusing on the ethical demand, the essay suggests that one can find spiritual guidance and strength to navigate challenging times.
Keywords: dementia; care; brother and sister; existential crisis; love; ethics